Islamic building regulations based on fatwa of Qadhi Al-Jamaah Ibn Abd Rafi’ (D 733h) / Sharifah Fadylawaty Syed Abdullah, Mohd Dani Muhamad and Siti Khadijah Ab. Manan - Syed Abdullah, Sharifah Fadylawaty; Muhamad, Mohd Dani; Ab. Manan, Siti Khadijah (Academy of Contemporary Islamic Studies (ACIS), 2016)
Fiqh rulings on built environment are not new in the classical Islamic architectural literature as the previous scholars had outlined specific hukm and guidelines relating to it. Nevertheless, limited literature is available on Islamic built environment at present, particularly on the issues relating to the maxim of ‘La Dharar Wa La Dhirar.' This paper is therefore aimed at analyzing the fundamental rulings on built environment in the context of ‘La Dharar Wa La Dhirar’. This study employed qualitative methodology via translation and content analysis from a selected classical Islamic book, namely ‘Mu’in AlHukkam’ by Qadhi Al-Jamaah Ibn Abd Rafi’. It is hoped that this study would eventually facilitate more understanding and awareness towards addressing issues of the built environment from Islamic perspectives. Furthermore, perhaps this exhibition will provide salient indicators or benchmark towards the improvement of built environment development in the future.